Separation of Gadolinium(III) from Terbium(III) by the Liquid-Liquid Extraction Method with Dibutyldithiophosphate as the Extractant - Senadi Budiman; Arie Hardian; Lisda Virdasari; Nurdeni Nurdeni; Herman Herman; Abdul Mutalib; Anni Anggraeni; Husein H. Bahti (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2022)
The purpose of this research is to separate gadolinium(III) from terbium(III), by the liquid-liquid extraction method, with the extractant dibutyl dithiophosphate. Gadolinium(III) and terbium(III) have been selected in this study to see if the two metallic ions still could be separated although they have only one difference in atomic number, and in fact, terbium (65Tb) is the next to gadolinium(64Gd), in the lanthanide series. Also besides, the two metals have been found together in the same mineral such as gadolinite, and in some other minerals in Indonesia. Extraction parameters have been firstly selected and extraction conditions have been optimized as well, using the experimental design of Plackett Burman. Thus, experiments have been done to select which of the nine parameters (i.e. Gd(III) and Tb(III) concentrations, the concentration of the extractant (dibutyl dithiophosphate), pH, volume ratio of aqueous phase to the organic phase, extraction temperature, shaking rate, shaking time, resting time (after shaking), have their significant effect on the extraction efficiency and separation. The data resulted from this study show that there were five of the nine factors studied that determine the extraction efficiency and separation. They were (with its respective optimum value in the bracket): Gadolinium concentration [Gd(III)](5 ppm), terbium concentration [Tb(III)](5 ppm), pH(3.0), shaking time (10 minutes), and rest time after shaking (10 minutes).